Assessing the Role of Remittances and Selected Major Macroeconomic Factors in South Asia's Economic Growth: Evidence from Panel Data Econometrics - Ali, Md. Hazrat; Pramanik, Sunamdeb Chandra; Hasan, Mehedi; Rahman, Shafika; Hossain, Md. Saddam (South Asian Journal of Social Sciences and Humanities, 2025)
This study investigates the role of remittances and major macroeconomic factors in driving  economic growth in South Asia, focusing on their interrelations and contributions using panel  data econometrics. The research employs a dataset of 160 observations from the World Bank,  including variables such as GDP, remittances, exports, imports, consumption, capital  formation, and inflation. A random effects regression model is utilized, selected through the  Hausman test for its robustness over a fixed effects approach. Stationarity tests confirm data  suitability for regression analysis. Results reveal that remittances positively and significantly  influence GDP, with a 1% increase in remittances leading to a 0.068% rise in GDP. Exports  and imports also bolster GDP growth, while inflation exerts a negative impact, highlighting the  critical need for macroeconomic stability. However, foreign direct investment (FDI) shows a  negative association with GDP, suggesting structural inefficiencies in the region's FDI  landscape. The study is constrained by the absence of data on informal remittance flows, which  may influence the comprehensiveness of the findings. The results underscore the need for  policymakers to optimize remittance utilization, enhance trade policies, and ensure  macroeconomic stability to sustain growth. Effective remittance management can enhance  household welfare and economic equity in South Asia, fostering inclusive development. This  research provides a nuanced analysis of remittances as a growth driver in South Asia,  emphasizing their interplay with trade and macroeconomic stability. It offers actionable  insights for sustainable economic development in the region.
Keywords: Remittances; Economic Growth; Macroeconomic Factors; South Asia; Panel Data